Performance/Media/Documentation... Thinking Beyond Dichotomies - Alessandro Cecchi (Sound Stage Screen, 2021)
The philosophical and general cultural contribution of Philip Auslander’s work to music, media, and the arts considered as performance is the radical, critical, and self-critical questioning of cultural dichotomies that often trap our thoughts exactly when they seem to help us think more clearly. Intervewed by Alessandro Cecchi, Auslander reflects on the exploration of the “continuum” between sound and vision, technique and technology, performance and media, music and the arts considered in their continuously and mutually changing relationships.